Зелена економіка: теоретичні аспекти - Марченко, Ольга Іванівна; Мамалига, Вікторія Олегівна; Марченко, Ольга (Східна Європа: економіка, бізнес та управління, 2019)
У статті розглянуто сутність економічної категорії «зелена економіка», її теоретичні аспекти, розглянуто головні три її складові – економічна, соціальна, екологічна. Обґрунтовано необхідність її розвитку в Україні. Розглянуто теоретичні і практичні засади впровадження «зеленої» економіки. Стверджується, що екологічна складова виступає пріоритетним напрямом сталого розвитку. Зроблено висновок, що серед напрямів реалізації зеленої економіки в Україні є раціональне використання природно-ресурсного потенціалу, використання досвіду розвинених європейських країн, які вже досягли значних успіхів у застосуванні принципів екологічної економіки, поєднання екологічної та економічної складових на усіх рівнях - регіональному, місцевому, національному, перехід на енергозберігаючі технології тощо. Досліджено економічний потенціал зеленої економіки, вказано на доцільність збільшення зелених інвестицій, залучення яких дозволить Україні вийти на якісно новий рівень розвитку.

Modern processes of modernization of the national economy of Ukraine face problems of scarcity of resources and pollution, which in the future negatively affect the factors of production. One of the areas of sustainable development of the national economy is the introduction of the so-called "green" economy, which contributes to the reduction of environmental and resource risks, as well as the attraction of private, public and international investments. It is the green economy that stimulates green growth, which, according to the OECD, is to identify green sources of growth, develop new green industries, create jobs and technology. This growth needs to stimulate investment and innovation that will underpin sustainable development and lead to new economic opportunities. The development of a "green" economy is the basis of sustainable economic growth and social stability, environmental protection and the conservation of resources for future generations. The terms "green energy" and "green economy" are now part of global trends. This is not surprising, as air pollution kills millions of people every year and causes enormous damage. In addition, oil, gas and coal reserves are depleting rather quickly.
Keywords: сталий розвиток; зелена економіка; навколишнє середовище; ресурсозбереження; природні ресурси; sustainable development; green economy; environment; resourcecon servation; natural resourses